Sleep difficulties and the relationship with depression, anxiety and stress in women - Ásrún Á. Jónsdóttir 1986- (2015)
There is a relationship between sleep difficulties and depression, anxiety, and stress that can have detrimental influences on a person’s daily functioning. This study aims to investigate this relationship among women, both mothers and non-mothers. Four hypotheses were tested and all but one were confirmed. The participants were 2475 women with the mean age of 32.5 years, including data from the study Mental health of women and childbirth and a comparison group with female students of Psychology at Reykjavik University in Iceland. The participants answered three psychological scales, the Depression Anxiety Stress Scales (DASS), the Edinburgh Postnatal Depression Scale (EPDS) and the Bergen Insomnia Scale (BIS). The results indicate that women screened with postpartum depression are more likely to suffer from mental distress and sleep difficulties in the future than women that were not screened with postpartum depression. The results also indicate that mothers are not more likely to suffer from mental distress or sleeping difficulties than students that are non-mothers, which could be caused by the ongoing stress students are faced with and irregular sleeping habits. The findings confirm that there is a strong relationship between sleep and mental distress. Það er samband á milli svefnerfiðleika og þunglyndis, kvíða og streitu sem getur haft alvarleg áhrif á daglegt líf einstaklings. Þessi rannsókn er gerð til að kanna þetta samband hjá konum, bæði mæðrum og ekki mæðrum. Fjórar tilgátur voru prófaðar og allar nema ein voru staðfestar. Þátttakendur voru 2475 konur með meðalaldurinn 32,5 ár og gögn úr rannsókninni geðheilsa kvenna og barneignir voru notuð ásamt samanburðarhópi sem innihélt kvenkyns nemendur við nám í Sálfræði við Háskólann í Reykjavík á Íslandi. Þátttakendur svöruðu þremur sálfræðilegum kvörðum, Depression Anxiety Stress Scale (DASS), Edinburgh Depression Scale (EPDS) og Bergen Insomnia Scale (BIS). Niðurstöðurnar gefa til kynna að konur sem skimast með fæðingarþunglyndi séu líklegri til að þjást ...